E ETIKA BERHIAS DALAM MASA IHDAD (IDDAH KEMATIAN): KAJIAN HUKUM ISLAM TERHADAP KONTEN KREATOR MUSLIMAH - Putri Siti Rahma; Said Syarifuddin Abu Baedah; Subaedah (El 'Ailaah, 2026)
This study aims to examine Islamic legal perspectives on women leaving the home for work during the iddah (mourning) period and to analyze scholarly understandings and fatwas regarding women adorning themselves during iddah. The research employs a qualitative approach through library research. Data are drawn from the Qur’an, hadith, classical and contemporary fiqh texts, tafsirs, scientific journals, and the Compilation of Islamic Law, analyzed using descriptive, normative, and contextual methods. The findings indicate that the basic ruling on adornment during iddah is prohibition, as it contradicts the essence of mourning. However, in professional contexts, there is room for leniency provided it avoids tabarruj (ostentatious display) and does not intend to attract public attention. Social media, as a digital public space, carries similar legal consequences to physical public spaces, thus requiring strict limitations on openly displayed adornment during iddah in accordance with Sharia principles. In conclusion, women may leave the home for work during iddah, and scholarly views permit makeup within tolerable limits.